Visual evoked potentials in 5 to 8-year-old children with retinopathy of prematurity - S.V. Katsan; O.Iu. Terletska; A.O. Adakhovska (Ukrainian Society of Ophthalmologists, 2020)
Background: The technique of visual evoked potentials (VEPs) is the only non-invasive method that can provide important diagnostic information regarding the functional integrity of the visual system. Purpose: To assess the electrical visual system activity in full-term children versus those with retinopathy of prematurity (ROP) using flash and pattern VEPs. Material and Methods: Sixty-four 5 to 8-year-old children (120 eyes) were examined, and their medical records were retrospectively reviewed and divided into three groups: Group 1 (full-term controls), 11 children (22 eyes); Group 2 (regressive ROP), 26 children (50 eyes), and Group 3 (treated with laser for type 1 pre-threshold ROP or aggressive posterior ROP), 27 children (48 eyes). Flash and pattern VEPs were recorded in all subjects. Results: There was a significant difference (p < 0.05) in P1 latency between Group 1 and Group 3, but not between Group 1 and Group 2 or between Group 2 and Group 3. In addition, there was a significant difference (p < 0.005) in P1 amplitude between Group 1 and Group 2, and between Group 2 and Group 3, but not between Group 2 and Group 3. Moreover, there was a significant difference (p < 0.05) in P100 latency for 1-degree and 0.15-degree check sizes between Group 1 and Group 3, but not between Group 1 and Group 2 or between Group 2 and Group 3. There was a significant difference (p < 0.05) in P100 amplitude for 1-degree check size between Group 1 and Group 2, and between Group 1 and Group 3, but not between Group 2 and Group 3. Finally, there was a significant difference (p < 0.05) in P100 amplitude for 0.15-degree check size between Group 1 and Group 2, and between Group 1 and Group 3, but not between Group 2 and Group 3. Conclusion: First, latencies and amplitudes of the P100 component of pattern VEP, and of the P1 component of the fVEP were determined for 5 to 8-year-old full-term children with the use of RETIscan (Roland Consult). Second, VEP characteristics (latencies and amplitudes of the P100 component of pattern VEP, and of the P1 component of the fVEP) for 5 to 8-year-old children who underwent timely laser photocoagulation (LPC) for ROP were found to be within the age-related norm. Finally, there was no significant difference in VEP characteristics between 5 to 8-year-old children with spontaneously regressed ROP and their peers who underwent LPC for severe ROP, which points to timeliness and efficacy of the performed LPC.